A Systematic Review on the Effect of Mechanical Stretch on Hypertrophic Scars after Burn Injuries - Yu-ting Zhang; Cecilia W.P. Li-Tsang; Ricky K.C. Au (SAGE Publishing, 2017)
Objective/Background: To review the effect of mechanical stretch on hypertrophic scars after burn injuries. Methods: A systematic review of all controlled trials related to the effect of mechanical stretch on post burn hypertrophic scars was conducted. Studies of conservative scar managements that applied mechanical forces parallel to the scar surface, including stretching exercise, massage, and splinting, were appraised. Eligible studies published in English between 1995 and 2016 were extracted from The Cochrane Library, MEDLINE, CINAHL, Science direct, SPORTDiscus, and Physiotherapy Evidence Database Scale (PEDro). The journals were further screened with inclusion and exclusion criteria. PEDro was selected for further analysis and appraisal. Results: There were 853 articles identified. After a standardized screening mechanism stipulated, only nine full-text articles were selected for critical appraisal using PEDro. There were five articles of high quality, two of fair quality, and two of poor quality. Detailed training regime and outcomes of nine studies were summarised, including two studies with stretching exercise, six studies with massage, and one study with splinting. The physical parameters of scar assessments and the range of motion on affected areas were compared. Conclusion: From extensive literature search, there was no strong evidence indicating the positive effect of mechanical stretch using stretching exercise, massage, or splinting on hypertrophic scars. A firm conclusion cannot be drawn for the discrepancy of outcome measures and varied effectiveness. Most of the included studies lacked objective evaluation or control group for comparison. Further high quality studies with larger sample size and using standardized measurements are needed.